PTU-035 Azathioprine metabolite concentrations in autoimmune hepatitis: relationship to disease remission. (28th May 2012) - Dhaliwal, H; Thornhill, E; Anderson, R; McFarlane, E; Gleeson, D; Lennard, L
Abstract : Introduction: Azathioprine (AZA) is used to maintain remission in AIH but is sometimes ineffective. AZA is a pro-drug and formation of active thioguanine nucleotide (TGN) metabolites varies widely. Competing with TGN formation is drug methylation, catalysed by thiopurine methyltransferase (TPMT). The methylated drug is inactive, but the methyl-mercaptopurine nucleotide metabolites (MeMPs) may not be. Previous studies, based mainly on single measurements, have not shown a relationship between TGN levels and clinical efficacy. We assessed the relationship between mean of several metabolite levels (TGNs and MeMPs), and therapeutic response in AIH patients prescribed a constant dose of AZA for remission maintenance. Methods: Erythrocyte TGNs and MeMPs were measured on serial blood samples by established techniques over 2 years. Average TGNs (avTGNs) and MeMPs (avMeMPs) concentrations for each patient at a constant AZA dose were analysed. Therapeutic response was defined as maintenance of remission on a given dose of AZA. Relapse was defined by the IAIHG criteria (ALT>2 × ULN or symptoms+ALT>ULN). Results: 349 samples from 68 patients (median 5, range 2–9, per patient) were analysed. Median avTGN concentration was 220 pmol/8×10 8 RBC (range 66–888) at a median dose of 1.9 mg/kg/day. AZA dose (mg/kg/day) correlated positively with avMeMPs (rs =0.38, p=0.001) but not with avTGN (rs =−0.06, p=0.6). Patients in whom remission was maintained compared to those who relapsed had higher avTGN concentrations (Abstract PTU-035 table 1) but avMeMPs concentrations were not significantly different. Mean ALT (both over the metabolite monitoring period and over the time on the constant AZA dose) correlated negatively with avTGN (rs =−0.322, p=0.007 and rs =−0.342, p=0.004) but not with avMeMPs. Patients who maintained a normal ALT had higher avTGN concentration compared to those who did not (median 237 vs 177 pmol/8×10 8 RBC). Conclusion: In patients with AIH maintained on AZA, lower average TGN concentrations are related to development of relapse and to higher ALT. Competing interests: None declared.